Flexible hybrid self-powered piezo-triboelectric nanogenerator based on BTO-PVDF/PDMS nanocomposites for human machine interaction - Wentao Dong; Mengyun Li; Chang Chen; Kun Xie; Jinhua Hong; Lin Yang (Scientific Reports)
Abstract As flexible and wearable electronics play more and more important role in smart watches, smart glass and virtual reality, and the power supply to the wearable electronics have been revealed more attentions for long-term usage and continuous healthy monitoring. To overcome the challenge, flexible self-powered BTO-PVDF/PDMS piezoelectric-triboelectric electric hybrid generators (BPP-HNG) are developed to human gesture monitoring and human machine interaction (HMI) application without external power supply. BPP-HNG based on BTO-PVDF and PDMS films are prepared by sol–gel and spin-coating method. When the BTO content is 20 wt.%, BPP-HNG exhibits better electrical performance with an output voltage of 20.51 V. A real-time gesture monitoring system is designed and developed to human machine interaction, which is able to control the motion of robot finger through BPP-HNG. BPP-HNG could monitor and recognize various gestures in real time, enabling synchronization between the human hand and the robot’s hand. With the convergence of AI technology and big data, BPP-HNG based HMI technology is expected to realize the potential of smarter and more intuitive interactions.